An energy efficient modified passive power filter for power quality enhancement in electric drives - Thentral, T. M. Thamizh; Usha, S.; Palanisamy, R.; Geetha, A.; Alkhudaydi, Ahmed M.; Sharma, Naveen Kumar; Bajaj, Mohit; Ghoneim, Sherif S. M.; Shouran, Mokhtar; Kamel, Salah (Frontiers in Energy Research, 2022)
In most industrial applications, AC drives are used. These drives require power electronic modules to convert AC to DC and also DC to AC. The power modules used for power conversion consist of power semiconductor switches. There is distortion in the voltage and current obtained from the power modules due to the non-linear behaviours of the semiconductor switches. To reduce the distortion in the input current, inductors are used along with the line impedance. A high value of inductance is required to maintain the percentage of THD within limits set by the latest standards. Along with the increased size and cost, it also reduces the power factor and output DC voltage at higher loads. The use of a passive power filter(PPF) is the conventional method followed for the reduction of % THD and improvement in power factor. PPFs comprise passive elements such as resistor, inductor and capacitor. These passive elements are connected at the point of common coupling (PCC) in shunt to compensate the harmonics present in the input current. In this paper a modified multi-tuned passive filter is considered to reduce the source current harmonics. A bridge rectifier with resistive load, three-phase induction motor drive and linear resistive-inductinve load is connected at the point of common coupling to zanalyze the harmonics present in the source current and also unbalance are created in one phase. To achieve the proper selection of resitance value for the passive filter, Class topper optimization technique is used. To validate the simulation results obtained for the multi-tuned passive filter, hardware is implemented with three-phase AC induction Motor drive load in which the speed of the motor is controlled with voltage by a frequency control algorithm using FPGA controller.